Public Awareness and Disciplinary Approaches to Managing Cultism in Nigerian Tertiary Institutions - Omemu, Felix (Faculty of Natural and Applied Sciences Journal of Basic and Environmental Research, 2025)
This study examines the perspectives of staff and students on the effectiveness of school disciplinary measures and public awareness campaigns in addressing cultism in Nigerian tertiary institutions. To direct the study, two hypotheses were examined using the t-test statistical analysis. 740 professors and 740 students who were chosen at random from universities in the states of Edo, Anambra, Ondo, Kwara, and Kano provided the data. The data was collected using a validated 10-item questionnaire. Staff and students' opinions of the efficacy of public awareness campaign tactics, including public lectures, symposiums, seminars, workshops, posters, handbills, and the use of print and electronic media, in combating cultism did not significantly vary, according to the results. Their opinions on the use of disciplinary actions, such as expulsion, suspension, and withdrawal, in dealing with cultism, however, differed significantly. These results led to the provision of useful advice.